Review: Nanotechnology- The secret of fifth industrial revolution and the future of next generation - SHIVANI RAI; ADITYA RAI (Smujo International, 2015)
Abstract. Rai S, Rai A. 2015. Nanotechnology - The secret of fifth industrial revolution and the future of next generation. Nusantara Bioscience 7: 61-66. Nanotechnology can be defined as a new and emerging technology with vast applications in the field of energy, electronic, cosmetics, textiles, medicine, agriculture, and environment, etc. In India, since post-independence both science and economics have progressed in the last century. Nanotechnology has filled various gaps in technologies and will develop all aspects of economy including wages, employment, market currencies, exchange rates supply and demand, etc. Nanotechnology with reduced size may allow for automation of tasks which were previously inaccessible due to physical restrictions. The industrial revolution has been evolved during the 16 century, and as result of which, the world economy has been changed drastically Now energy resources and manufacturing play pivotal role in the development of economy and technologies. The new innovations of nanotechnology will change the scenario of the poor people with the power of economy. Today, we would be able to change the world by “The fifth industrial revolution of nanotechnology”. The more striking is that it will cover-up the target ratio of economy since quarter century and accomplish the target ratio of economy within ten years. However, nanotechnology may have exerted toxicity. This may be harmful to nature and living organisms Apart from that, there are some other implications such as ethical issues, which may in turnoff footsteps back and raises certain issues. In fact, there is a need for awareness among the common people in society. The focus of the present review is to discuss role of nanotechnology that is quite augmented in different industries and also in generating fifth revolution leading to better future of next generation.